Life on the Mississippi, Part 10. - Twain, Mark, 1835-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"Life on the Mississippi, Part 10." by Mark Twain is a memoir published in 1883. It recounts Twain's experiences as a young steamboat pilot on the Mississippi River before the Civil War, detailing his apprenticeship under veteran pilot Horace Bixby. The work also chronicles his return journey years later, observing how the river and its towns have transformed. Twain blends personal anecdotes, navigational expertise, tall tales, and social commentary on American progress and excess along the mighty waterway. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Life_on_the_Mississippi
Release date is 2004-07-10
Produced by David Widger
Keywords: Mississippi River -- Description and travel; Mississippi River Valley -- Social life and customs -- 19th century; Authors, American -- 19th century -- Biography; Pilots and pilotage -- Mississippi River; Twain, Mark, 1835-1910 -- Travel -- Mississippi River